4CPS-190 Evaluation of a new clinical pharmacy service within a newly launched surgical admission process. (24th March 2020) - Kreundl, K; Koch, K; Sablatschan, C; Klems, M; Kirchdorfer, K; Lemmens, R; Mueller, D
Abstract : Background and importance: Clinical pharmacy services (CPS) targeting the admission of surgical patients have been shown to provide significant benefit for patient safety and care. Aim and objectives: To evaluate a CPS within a newly launched integrated admission process for elective surgery patients: (1) by defining the number and type of identified drug related problems (DRPs) and acceptance rate of pharmacists' suggestions for medication optimisation; and (2) by assessing the perception of the service and identifying barriers and optimisation potential. Material and methods: This was a retrospective descriptive analysis of number and type of identified DRPs, suggested interventions and their acceptance rate based on a validated classification system. 1 We also determined the health professions' perceptions towards the new service, measured using a piloted self-administered quantitative questionnaire. The setting was a 450 bed teaching hospital, with an on-site service implemented within a central integrated admission process for elective patients across four surgical wards. All patients receiving the CPS in the data collection period (April–December 2018) were included. Questionnaires addressed medical and nursing staff on covered surgical wards (4 week data collection period). Results: Pharmacists reviewed 1877 patient files (6214 drugs) and identified 2003 DRPs, on average 1.07 DRP/patient. The most common DRPs were drug interactions (31%), drug without indication (20%), need for monitoring (14%) and untreated indication (11%). The most common recommended interventions were drug monitoring (30%), starting a drug (13%) and stopping a drug (13%), and advisory information was provided (17%). Overall, 22% of interventions were implemented. Identified barriers were lack of awareness of the pharmacists' e-consults, limited time resources and the surgical setting. The questionnaire confirmed the benefits, indicating patient safety, medicine optimisation and reduced workload for medical staff. The CPS was rated as 'good'. Conclusion and relevance: The high prevalence of identified DPRs reflected the contribution of the CPS towards improved patient safety and care. The questionnaire highlighted the value and acceptance of the CPS by other health professions and identified barriers to further adaption. The acceptance rate can be perceived as successful considering the limitations of the short on-site stay of surgical patients and the recent implementation of the CPS in April 2018. Hence the data showed clear benefits. The role of the clinical pharmacist within the central admission process should be further established to exploit further potential for CPS in this field. References and/or acknowledgements: 1. Allenet B, et al. Pharm World Sci 2006;28:181–188. No conflict of interest.